Neutrophil-lymphocyte and platelet-lymphocyte ratios as systemic inflammatory biomarkers for atopic dermatitis in US adults: a cross-sectional NHANES study revealing subgroup heterogeneity - Chen, Xuanlin; Yang, Xiangyu; Zhang, Min; Zhao, Yirui; Guo, Shuping (Frontiers in Immunology, 2025)
BackgroundNeutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are systemic inflammation markers, but their association with adult atopic dermatitis (AD) remains underexplored.MethodsThis cross-sectional study analyzed 2001–2006 NHANES data from 10,890 US adults. AD was defined by self-reported physician diagnosis. Cutoffs for NLR (1. 81×109/L) and PLR (136. 13×109/L) were determined via ROC analysis. Multivariable models adjusted for sociodemographic and clinical covariates.ResultsElevated NLR (≥1. 81×109/L) and PLR (≥136. 13×109/L) were independently associated with higher AD prevalence after full adjustment (NLR: OR=1. 23, 95%CI:1. 08–1. 40; PLR: OR=1. 24, 95%CI:1. 10–1. 41). Subgroup analyses revealed stronger associations in males, normal-BMI individuals, and asthmatics (PLR: OR=1. 84), but inverse correlations in nonsmokers (NLR: OR=0. 33; PLR: OR=0. 34). Significant interactions occurred with BMI and asthma (PLR-interaction P=0. 0077).ConclusionNLR and PLR are accessible systemic inflammatory biomarkers for AD, with subgroup heterogeneity suggesting roles for lymphocyte depletion (skin homing), neutrophilic (Th17), and platelet-mediated (Th2) inflammation pathways.